Medicago truncatula esn1 Defines a Genetic Locus Involved in Nodule Senescence and Symbiotic Nitrogen Fixation - Jiejun Xi; Yuhui Chen; Jin Nakashima; Suo-min Wang; Rujin Chen (Molecular Plant-Microbe Interactions, 2013)
Symbiotic interaction between Medicago truncatula and Sinorhizobium meliloti results in the formation on the host roots of new organs, nodules, in which biological nitrogen fixation takes place. In infected cells, rhizobia enclosed in a plant-derived membrane, the symbiosome membrane, differentiate to nitrogen-fixing bacteroids. The symbiosome membrane serves as an interface for metabolite and signal exchanges between the host cells and endosymbionts. At some point during symbiosis, symbiosomes and symbiotic cells are disintegrated, resulting in nodule senescence. The regulatory mechanisms that underlie nodule senescence are not fully understood. Using a forward genetics approach, we have uncovered the early senescent nodule 1 (esn1) mutant from an M. truncatula fast neutron-induced mutant collection. Nodules on esn1 roots are spherically shaped, ineffective in nitrogen fixation, and senesce early. Atypical among fixation defective mutants isolated thus far, bacteroid differentiation and expression of nifH, Leghemoglobin, and DNF1 genes are not affected in esn1 nodules, supporting the idea that a process downstream of bacteroid differentiation and nitrogenase gene expression is affected in the esn1 mutant. Expression analysis shows that marker genes involved in senescence, macronutrient degradation, and remobilization are greatly upregulated during nodule development in the esn1 mutant, consistent with a role of ESN1 in nodule senescence and symbiotic nitrogen fixation.